Simulation in Critical Care Medicine: A Meta-analysis - Wesam A. Alhejily, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Simulation is a recognized method of teaching in academic medicine. Despite its long availability, only a paucity of information exists regarding its efficacy and utility on patient care and subsequently on patient outcomes. In this meta-analysis, we attempt to systematically study the effect of simulation-based clinical teaching in critical care medicine. A review of literature was conducted, looking across several databases, for any available studies that compare simulation to standard methods of teaching in the setting of critical care medicine on three surrogate outcomes: enhancement of knowledge, improvement in skills, and patient outcomes. In this study, 508 articles were found at the initial screening, however only 14 articles were eligible after applying our inclusion and exclusion criteria. Of these 14 articles only 5 were found to be randomized control trials and their outcomes were either knowledge or skill enhancement, no study on patient outcome was identified. Despite the significant heterogeneity between studies (?2 (4) = 120.73) p < 0.001), the random effect was significant on both surrogate markers (p < 0.001). As a conclusion, albeit only a few randomized trials, simulation has a positive impact on knowledge and skill acquisition in the field of critical care medicine.